High-resolution magnetic and palynological records of the last deglaciation and Holocene from Lake Xiarinur in the Hunshandake Sandy Land, Inner Mongolia. (May 2015) - Tang, Ling; Wang, Xisheng; Zhang, Shuqin; Chu, Guoqiang; Chen, Yun; Pei, Junling; Sheng, Mei; Yang, Zhenyu
High-resolution mineral magnetic and pollen records from overlapping piston cores from Lake Xiarinur (42°37′N, 115°28′E) document detailed changes in environment and vegetation since the last deglaciation in the Hunshandake Sandy Land, Inner Mongolia. The formation of Lake Xiarinur commenced during the Bølling–Allerød warming, as reflected by an abrupt shift in sedimentary facies from eolian sands to lacustrine sediments at a core depth of 3.5 m (~14.1 cal. kyr BP). The pollen records demonstrate that desert vegetation with sparse herbs occurred before 14.1 cal. kyr BP, which was succeeded by meadow grassland vegetation from ~14.1 –13.3 cal. kyr BP (the Bølling -Allerød). A dramatic decrease in pollen concentration occurred between ~13.3 and 11.7 cal. kyr BP corresponding to the Younger Dryas. The remarkable increases in pollen and Pediastrum concentrations at ~11.7 cal. kyr BP suggest that the environment began to ameliorate, and the most humid conditions prevailed until ~8.5 cal. kyr BP. The maxima of magnetic concentration–dependent and magnetic-grain-size-dependent parameters, together with high pollen concentrations, between ~10 and 9 cal. kyr BP are interpreted as a brief interval of high annual precipitation. Our results indicate a stepwise decrease in effective moisture in the mid-Holocene and an accelerated drying trend in the late Holocene, characteristics typical of an East Asian summer monsoon–influenced region. The broad similarities between our data and other lake records from central-eastern Inner Mongolia, well-dated speleothem δ 18 O records from southern and central China, and summer insolation at 45°N, support the idea that vegetation and climate changes in the Hunshandake Sandy Land were controlled mainly by fluctuations in the response of the East Asian monsoon to Northern Hemisphere summer insolation.